Examining the Impact of Platform Usage on Online Purchasing in E-commerce - Halim, Fransiscus Ati; Djong, Darren Irawan; Usman, Sabrina Fajrul Ula (Universitas Multimedia Nusantara, 2023)
With the increasing number of consumers from diverse backgrounds engaging in online purchasing, e-commerce platforms such as Tokopedia, Shopee, TikTok Shop, and others play a significant role. This research aims to examine the influence of e-commerce platform usage on consumer preferences. A descriptive quantitative methodology was employed, utilizing a Google form questionnaire distributed among the researcher's immediate surroundings. The research findings indicate that several factors have a notable impact on users' preferences when making online purchases.